Deletion of Ascl1 in pancreatic β-cells improves insulin secretion, promotes parasympathetic innervation, and attenuates dedifferentiation during metabolic stress - Anna B. Osipovich; Frank Y. Zhou; Judy J. Chong; Linh T. Trinh; Mathew A. Cottam; Shristi Shrestha; Jean-Philippe Cartailler; Mark A. Magnuson (Molecular Metabolism, 2023)
Objective: ASCL1, a pioneer transcription factor, is essential for neural cell differentiation and function. Previous studies have shown that Ascl1 expression is increased in pancreatic β-cells lacking functional KATP channels or after feeding of a high fat diet (HFD) suggesting that it may contribute to the metabolic stress response of β-cells. Methods: We generated β-cell-specific Ascl1 knockout mice (Ascl1βKO) and assessed their glucose homeostasis, islet morphology and gene expression after feeding either a normal diet or HFD for 12 weeks, or in combination with a genetic disruption of Abcc8, an essential KATP channel component. Results: Ascl1 expression is increased in response to both a HFD and membrane depolarization and requires CREB-dependent Ca2+ signaling. No differences in glucose homeostasis or islet morphology were observed in Ascl1βKO mice fed a normal diet or in the absence of KATP channels. However, male Ascl1βKO mice fed a HFD exhibited decreased blood glucose levels, improved glucose tolerance, and increased β-cell proliferation. Bulk RNA-seq analysis of islets from Ascl1βKO mice from three studied conditions showed alterations in genes associated with the secretory function. HFD-fed Ascl1βKO mice showed the most extensive changes with increased expression of genes necessary for glucose sensing, insulin secretion and β-cell proliferation, and a decrease in genes associated with β-cell dysfunction, inflammation and dedifferentiation. HFD-fed Ascl1βKO mice also displayed increased expression of parasympathetic neural markers and cholinergic receptors that was accompanied by increased insulin secretion in response to acetylcholine and an increase in islet innervation. Conclusions: Ascl1 expression is induced by stimuli that cause Ca2+-signaling to the nucleus and contributes in a multifactorial manner to the loss of β-cell function by promoting the expression of genes associated with cellular dedifferentiation, attenuating β-cells proliferation, suppressing acetylcholine sensitivity, and repressing parasympathetic innervation of islets. Thus, the removal of Ascl1 from β-cells improves their function in response to metabolic stress.